Can Quetiapine Prolong the Antidepressant Effect of Ketamine?: A 5-Year Follow-up Study. Issue 6 (November 2021) - Amiaz, Revital; Saporta, Rachel; Noy, Adam; Berkenstadt, Haim; Weiser, Mark
Abstract: Purpose: Ketamine, a noncompetitive, high-affinity antagonist of the N -methyl-D-aspartate-type glutamate receptor, has a rapid effect in patients with treatment-resistant disorder, but many patients who respond to intravenous ketamine relapse within several days. The objective of this study was to examine the long-term outcome of patients' mood 5 years after ketamine treatment. Methods: Sixteen electroconvulsive therapy referrals received at least 1 intravenous ketamine treatment in addition to their stable antidepressant medications. Depression was evaluated using the Inventory of Depressive Symptomatology–Clinician-Rated, Hamilton Rating Scales for Depression, and Montgomery-Åsberg Depression Rating Scale. Anxiety was measured using the Hamilton Rating Scale. Results: Of 16 patients treated, 6 achieved complete remission, 3 partially responded, and 7 did not respond. At baseline, all patients were treated with antidepressants, 14 patients were also treated with neuroleptics, of whom 5 patients were treated with quetiapine. The time to relapse in the 5 patients taking quetiapine was significantly longer than in patients who were taking other neuroleptics (965.83 ± 824.68 vs 80.5 ± 114.3, Z = 7.001, P = 0.0001). At the 5-year follow-up, 3 of the patients taking quetiapine maintained their remission. Overall levels of depression and anxiety at all times were improved in comparison to baseline. Conclusions: Our follow-up results suggest that the combination of quetiapine and ketamine can prolong time to relapse after ketamine treatment in patients with treatment-resistant disorder.